1994
DOI: 10.1002/ajmg.1320510422
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis at the FRAXA locus in the Japanese population

Abstract: Fragile X syndrome, one of the most common human genetic diseases, is characterized by a unique genetic mechanism which involves dynamic mutation in a heritable unstable DNA sequence, a p(CCG)n repeat, in the FRAXA locus. It has recently been suggested that a few founder chromosomes are responsible for most fragile X mutations in the Caucasian population. In order to investigate the origin of the fragile X mutations in the Japanese population, we analyzed haplotypes of the FRAXA locus in 40 unrelated fragile X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
7
20
1
Order By: Relevance
“…The FRAXAC1-106 bp allele was present in 62 % of the total Indonesian population compared with 15-22 % in the Caucasian population Kunst et al 1996). In all Asian populations studied to date, the 106 bp allele has approximately twice the frequency of the 108 bp allele, whereas in Caucasians and Africans the 108 bp allele predominates (Richards et al 1994 ;Zhong et al 1994 ;Chiurazzi et al 1996 b ;Poon et al 1999). Despite the similar trends, the observed differences in the allele frequencies between the Malay and Chinese populations reached statistical significance for the FMR1 CGG repeat and FRAXAC1, while the Melanesian Indonesian subgroup is even more divergent.…”
Section: mentioning
confidence: 89%
See 2 more Smart Citations
“…The FRAXAC1-106 bp allele was present in 62 % of the total Indonesian population compared with 15-22 % in the Caucasian population Kunst et al 1996). In all Asian populations studied to date, the 106 bp allele has approximately twice the frequency of the 108 bp allele, whereas in Caucasians and Africans the 108 bp allele predominates (Richards et al 1994 ;Zhong et al 1994 ;Chiurazzi et al 1996 b ;Poon et al 1999). Despite the similar trends, the observed differences in the allele frequencies between the Malay and Chinese populations reached statistical significance for the FMR1 CGG repeat and FRAXAC1, while the Melanesian Indonesian subgroup is even more divergent.…”
Section: mentioning
confidence: 89%
“…Although the frequencies of non-106 and 108 bp FRAXAC1 and 200 bp DXS548 alleles are low in Indonesians (3 % and 1 % respectively) studies of allele diversity in Chinese and Japanese have shown that these populations have a much more restricted allele repertoire at these loci (Zhong et al 1994 ;Richards et al 1994 ;Poon et al 1999). We speculate that this may be the result either of the presence of indigenous populations in Sundaland prior to the Austronesian migration from Taiwan\southern China 5000-6000 years ago, or due to other genetic admixtures from migrations and colonisations from the Indian subcontinent, southern Asia and Oceania.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…These reports include cohorts from Asia, Europe, and North America. The modal repeat length is 29 and 30 CGGs in most of these reports, with the exception of 2 Japanese studies (modal value was 27 or 28 CGG repeats), 14,19 a study of Canadian newborns (modal value was 28), 16 and a study of Israeli men (modal value of 27). 12 Five of these articles reported separate results for females.…”
Section: Existing Population Data In the Range Ofmentioning
confidence: 99%
“…This is very similar to distributions reported for Asian populations. [20][21][22] Comparison of (CGG) n allele sizes and linked DXS548-FRAXAC1 haplotypes showed that 85% of alleles with 29-31 CGG were linked to haplotype 7-3 Analysis of FRAXA alleles in the population of Greenland t and 88% of alleles with 35-37 CGG were linked to haplotype 6-4 ( Figure 1). …”
Section: Distribution Of (Cgg) N Alleles and Dxs548-fraxac1 Haplotypementioning
confidence: 99%